Factors Influencing Young Women’s Intention to Undertake Science, Technology Engineering and Mathematics (STEM) Education: A Review of Literature - Sajid, Sadia; Sultana , A.M.; Kok , Jin Kuan; Kok , Jin Kuan; Rehman, Mobashar (International Journal of Psychosocial Rehabilitation, 2020)
Globally, women are underrepresented in science, technology, engineering and mathematics (STEM) fields. Although women’s participation in higher education is increasing, they are still significantly underrepresented in STEM fields. The under-representation of women in STEM translates into the loss of a critical mass of talent, thoughts and ideas, which hinders countries from reaching their maximum developmental potential. It is important to understand the forces at play, which drive women’s choice of STEM education. This could be due to a variety of reasons, including personal (I.e. self-concept, self-efficacy, personal preferences, self-stereotyping and intrinsic motivation) as well as the external factors (i.e. role models, family, teacher’s influence as well as low recruitment of women in STEM fields). This paper systematically reviews the literature on young women’s intention to undertake STEM education in Malaysian context. The paper also highlights those personal and external factors which have not been studied extensively in Malaysian context. This paper can give readers a novel insight about factors influencing women’s participation in STEM education in Malaysia.